Candida Species Distribution of Clinical Specimens in Banda Aceh, Indonesia - Suhartono, Suhartono; Mahdani, Wilda; Masthura, Aderiana; Rusmana, Iman (Biosaintifika: Journal of Biology & Biology Education, 2020)
Candidiasis has become increasingly widespread in the community alongside with the developing resistance of Candida sp. to some antifungals. A prevalence study in the present research is required to surveil the distribution of Candida-related infections to administrate the appropriate antifungal treatments. The objective of this research was to determine the species distribution of candidiasis with their antifungal susceptibility isolated from clinical specimens at the Zainoel Abidin Hospital (ZAH) Banda Aceh, Indonesia. The clinical specimens were from inpatients and outpatients in the hospital during January to June 2019. The identification of Candida species and antifungal sensitivity assay were conducted by using VITEK® 2 Compact. Of a total of 68 isolates, there were six species of Candida with the highest species prevalence was Candida tropicalis (52.94%). Additionally, the highest prevalence of candidiasis came from urine specimen (54.41%) and mostly from inpatients in the internal medicine unit (54.41%). Candidiasis occurred predominantly in men (58.82%) and during adulthood (55.88%). The antibiogram of Candida sp. shows a high percentage of sensitivity towards some antifungals including fluconazole (100%), voriconazole (100%), caspofungin (100%), micafungin (100%), amphotericin B (99.5%), and flucytosine (100%). From this result, it can be concluded that candidiasis cases in the ZAH Banda Aceh, Indonesia has prevalently occurred with the few antifungal therapies for candidiasis of were still effective empirically and definitively. This is an initial study of Candida prevalence within different clinical samples in Banda Aceh and the study is expected to be a basis for prevention and control of Candida-related infections in the area.